Ocular abnormalities in healthy Standardbred foals. (3rd September 2012) - Barsotti, Giovanni; Sgorbini, Micaela; Marmorini, Paola; Corazza, Michele
Abstract: Objective To determine the prevalence and describe ocular abnormalities in healthy Standardbred foals within 48 h of birth. Animals One hundred and two neonatal foals. Procedures All foals had an unassisted delivery. On the basis of physical examination and the results of hematological and biochemical parameters, all foals were unaffected by systemic diseases. A complete ophthalmic examination was performed within 48 h of birth. Foals with ocular hemorrhages were re‐examined weekly until the abnormalities were resolved. Results 65/102 (63.7%) foals did not show ocular abnormalities, while in 37/102 (36.3%) cases, ocular abnormalities were present. Retinal and subconjunctival hemorrhages were recorded in 19/102 (18.6%), and in 13/102 (12.7%), respectively. In 4/102 (3.9%) animals, an entropion of the lower eyelid was present. Only one foal (1%) showed a congenital nuclear unilateral cataract. No other ocular abnormalities were detected. However, all foals showed various degrees of remnants of hyaloid system. One week after the first ocular examination, retinal hemorrhages had resolved in 100% of the eyes, whereas subconjunctival hemorrhages had disappeared in all eyes by the second week following the first examination. Conclusions The acquired ocular lesions observed with relatively high frequency in the examined healthy Standardbred foals were ocular hemorrhages, which always showed a good outcome. Although these abnormalities were present at birth, they were not considered strictly congenital but likely acquired during parturition. Instead, congenital ocular abnormalities were rarely diagnosed, and the entropion of the lower eyelid was the most common disease in the breed.